2013
DOI: 10.1097/prs.0b013e318277856f
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Outcome and Cost Analysis of Free Tissue Transfer for Breast Reconstruction

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
88
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 21 publications
1
88
1
2
Order By: Relevance
“…Fischer et al, in 2013, found that autologous reconstructions, flap type, anemia, ASA physical status C 3, obesity, and active smoking were associated with higher surgical complications during the first 30 days post-immediate reconstruction [15][16][17]. Obesity, chronic obstructive pulmonary disease, and hypertension were associated with major delayed surgical complications [15]. Mioton et al, in 2013, found that autologous reconstruction, when compared to prosthetic reconstruction, had higher rates of 30-day overall complications, wound infection, prosthesis/flap failure, and reoperation [18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fischer et al, in 2013, found that autologous reconstructions, flap type, anemia, ASA physical status C 3, obesity, and active smoking were associated with higher surgical complications during the first 30 days post-immediate reconstruction [15][16][17]. Obesity, chronic obstructive pulmonary disease, and hypertension were associated with major delayed surgical complications [15]. Mioton et al, in 2013, found that autologous reconstruction, when compared to prosthetic reconstruction, had higher rates of 30-day overall complications, wound infection, prosthesis/flap failure, and reoperation [18].…”
Section: Discussionmentioning
confidence: 98%
“…Fischer et al, in 2013, found that autologous reconstructions, flap type, anemia, ASA physical status C 3, obesity, and active smoking were associated with higher surgical complications during the first 30 days post-immediate reconstruction [15][16][17]. Obesity, chronic obstructive pulmonary disease, and hypertension were associated with major delayed surgical complications [15].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies evaluating immediate autologous tissue-based reconstruction before PMRT have reported reasonable rates of complications and satisfactory cosmetic outcomes. 6,29,30,38 However, overall complication rates are often imprecisely defined, as reported overall complications may include complications at both the donor and recipient sites. 39 Even overall complication rates for only the recipient site are not significantly affected by PMRT, especially since radiation therapy is not typically begun until 1 or 2 months after the transfer of the microvascular flap.…”
Section: Discussionmentioning
confidence: 99%
“…However, muscle-conserving abdominal flaps may have an advantage in reducing morbidity. [17][18][19][20][21][22] The main findings of the present prospective study are that 15 of 16 patients (94 percent) were discharged from the hospital within 72 hours of surgery. Only the use of suction drains and the need for flap monitoring prevented patients from being discharged by the afternoon of the second postoperative day.…”
Section: Discussionmentioning
confidence: 99%